2016
DOI: 10.1177/0305735616652954
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers’ attribution of affect to music: A comparison between vocal and instrumental performance

Abstract: Research has shown inconsistent results concerning the ability of young children to identify musical emotion. This study explores the influence of the type of musical performance (vocal vs. instrumental) on children's affect identification. Using an independent-group design, novel child-directed music was presented in three conditions: instrumental, vocal-only, and song (instrumental plus vocals) to 3-to 6-year-olds previously screened for language development (n = 76). A forced-choice task was used in which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 104 publications
(144 reference statements)
0
16
0
Order By: Relevance
“…This process of development is not clearly paralleled in music. While some studies have found evidence for discrimination of valence expressed by music in children as young as 3 years, most studies have found that the ability to discriminate happy from sad musical excerpts above chance starts to emerge at some point around 4 or 5 years of age ( Dolgin and Adelson, 1990 ; Adachi and Trehub, 1998 ; Mote, 2011 ; Stachó et al, 2013 ; Franco et al, 2016 ; but see Cunningham and Sterling, 1988 ; and Hunter et al, 2011 , for two studies that found this ability only in later ages). Notably, the ability emerges around the same age when they develop the ability to entrain to musical rhythms, suggesting that tempo variations play a central role in the ability to distinguish these two expressions both in speech and music ( Dalla Bella et al, 2001 ).…”
Section: Does Music Express Basic Emotions?mentioning
confidence: 99%
See 1 more Smart Citation
“…This process of development is not clearly paralleled in music. While some studies have found evidence for discrimination of valence expressed by music in children as young as 3 years, most studies have found that the ability to discriminate happy from sad musical excerpts above chance starts to emerge at some point around 4 or 5 years of age ( Dolgin and Adelson, 1990 ; Adachi and Trehub, 1998 ; Mote, 2011 ; Stachó et al, 2013 ; Franco et al, 2016 ; but see Cunningham and Sterling, 1988 ; and Hunter et al, 2011 , for two studies that found this ability only in later ages). Notably, the ability emerges around the same age when they develop the ability to entrain to musical rhythms, suggesting that tempo variations play a central role in the ability to distinguish these two expressions both in speech and music ( Dalla Bella et al, 2001 ).…”
Section: Does Music Express Basic Emotions?mentioning
confidence: 99%
“…In fact, children’s ability to discriminate happy, sad, angry, and fearful expressions in music starts to appear around 6 to 8 years of age ( Kastner Pinchot and Crowder, 1990 ; Kratus, 1993 ; Gerardi and Gerken, 1995 ; Dalla Bella et al, 2001 ; Nawrot, 2003 ), and their ability only reaches adult-like performance in emotion discrimination tasks of music much later: around age 11 ( Hunter et al, 2011 ). The disagreements on the exact age where these abilities emerge may be attributed to differences in stimuli, procedure, and response formats used in each study (see Franco et al, 2016 for a review of these methods). However, beyond this variety, a developmental milestone that happens between 6 and 8 years of age explains the gradual development of discriminating several emotions expressed by music: the acquisition of sensitivity to mode, a musical cue associated with the expression of negative emotions in Western music ( Gregory et al, 1996 ).…”
Section: Does Music Express Basic Emotions?mentioning
confidence: 99%
“…Basically, teachers need to be skilled to analyse the content of lessons that they want to convey and compose the lyrics according to the topic, the environment, or the ability of the child. Usually, children are quiet because he/she wants to interact with others in the way of communication he/she knows; the rhythmic method is an approach that could stimulate the mind and create multilateral interactions among children if they learn in group (Franco et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Learning through rhythmic techniques is a friendly and interesting way of attracting children (Franco, Chew, & Swaine, 2017). Indeed, children are a group of people who love singing and moving (Shenfield, Trehub, & Nakata, 2011).…”
Section: Application Of Rhythmic Techniques In Teaching Maintaining Tmentioning
confidence: 99%
“…Overall, it appears that by 5 or 6 years old, children tend to agree with adults about basic emotions expressed in orchestral music, including happiness , sadness , anger , and fear , although the latter two are often confused (Cunningham & Sterling, 1988; Giomo, 1993; Kratus, 1993; Terwogt & van Grinsven, 1991; Vidas, Dingle, & Nelson, 2018). Other studies have reported successful recognition of happiness , sadness , and anger by children as young as 3 or 4 years old (Franco, Chew, & Swaine, 2016; Gentile, 1998) , and several studies found that infants as young as 5 months old could discriminate between excerpts that had been selected previously by adults and pre‐schoolers as representative of happy and sad (Flom, Gentile, & Pick, 2008; Flom & Pick, 2012). However, from these studies, it is impossible to know which expressive cues pre‐schoolers used in their judgments, and whether infant discrimination was based on differences in perceived affect per se or simply on differences in certain salient acoustic cues (for example, tempo differences between the happy and sad excerpts).…”
Section: Introductionmentioning
confidence: 99%